The Effect of Using Robot Waiters in Restaurants on Consumers' Behavioral Intentions - İbrahim Aydın; Zübeyir Çelik (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
This study examines the effect of using robot waiters in restaurants on consumers' behavioral intentions. For this aim, data were collected from 385 people using online questionnaire and experiment method. The data were analyzed using the SPSS 25 package program. According to the one-sample t-test result; using robot waiters is not a significant predictor of consumers' intentions to use robotic restaurants. In addition, according to independent samples t-test results; between female and male, and also according to the results of ANOVA for independent groups; between X, Y, and Z generations, there is no significant difference in consumers' intention to use robotic restaurants. However, according to the results obtained by simple linear regression analysis; the perceived innovativeness of using robotic restaurants, as well as the perceived value, perceived enjoyment, and attractiveness of using robot waiters, are positive and important predictors of attitude towards using robotic restaurants. In addition, the attitude towards using the robotic restaurant is a positive and important predictor of both the intention to use the robotic restaurants and the willingness to pay more to use the robotic restaurants. At the end of the study, suggestions were made within the framework of limitations.